In vitro and in situ evaluation of the effects of high-fluoride and arginine-based toothpastes to control root caries - Velo, Marilia Mattar de Amoêdo Campos (2017)
The focus of our studies has been the root substrate dentin, once root caries prevalence has been reported as increasing in part due to people living longer and maintaining their natural teeth into old age. Furthermore, this condition is highly prevalent in patients undergoing head-and-neck radiotherapy (HNR). To better understand the effect of different toothpastes in sound and non-irradiated root dentin, this research was developed in 3 parts with specific objectives, involving both in nonirradiated and irradiated substrates. In study 1, high-F toothpaste (5,000 g F/g) associated or not with f tri-calcium phosphate (f TCP) were compared in vitro with conventional one (1,450 g F/g) to control bovine root caries development. The study 2 was conducted to evaluate if the in vitro performance would be similar in a closer clinical situation. An in situ design was performed and the effect of high-F toothpaste combined or not with f TCP comparing to 1,450 g F/g combined or not with argininebased toothpastes in reducing the net demineralization of sound root dentin and on the remineralization in initial artificial caries lesions was verified. In study 3, the effects of radiation exposure on human root dentin composition, structure and mechanical properties were evaluated. In the first study, our findings highlight the importance of using high-F toothpastes to prevent root caries development. In the second one, the results showed great performance of high-F toothpastes and arginine-based toothpastes, in clinical situations. The results of study 3 showed that radiation exposure changed the composition and structure of human root dentin, which may detrimentally affect its mechanical properties. Overall, the studies suggest that at high-risk population, such as elderly people and patients undergoing HNR, it is important to develop protocols to minimize damages caused by carious lesions, inhibiting the net demineralization of root caries. The current results can clarify the effects of radiation on root dentin to help further studies in this area. We also could observe that conventional toothpaste is not as effective as high-F toothpastes to prevent this condition, in non-irradiated root dentin. This knowledge is of special interest to determine the quality of life of high-risk population to dental caries presenting available tools that can be of at-home use with beneficial effects on demineralization protection and reversion.